MASLAHAT DANA DESA DALAM PEMBANGUNAN MASYARAKAT MADANI DI KECAMATAN POSIGADAN KABUPATEN BOLAANG MONGONDOW SELATAN - Sahabi, Ansar; Dewi Yusuf, Sri; Mohamad, Roni; S, Syawaluddin (Program Studi Manajemen Keuangan Syariah, 2022)
This study aims to see the benefits of Village Funds in Civil Society Development in Posiga and South Bolaang Mongondow Districts. The community has become the main source in developing and advancing the village from what was proclaimed by the Central and Regional governments which were promoting regional autonomy. In particular, the sub-districts where the Village Fund is utilized are really absorbed for development and community empowerment in order to achieve prosperity and equalization of economic capacity to realize development and community empowerment based on local culture achieved by each region, so that healthy and dynamic conditions will grow. , which will ultimately lead to civil society. This study uses a qualitative method with a descriptive approach. Data collection techniques through observation, and interviews. Data analysis used is data reduction, data presentation, and drawing conclusions. The results show that the priority of village funds in improving rural development runs optimally in accordance with what is expected by the government and village communities in Posigadan sub-district. Utilization of village funds in the field of community empowerment is really used for budget priorities such as, each absorbed in the trade and industry sub-sector, marine and fisheries sub-sector, agriculture and animal husbandry sub-sector, BUMDes management training, facilities, productive economic business training, holding village exhibitions, increasing food crop production, increasing village apparatus capacity, and developing Micro, Small and Medium Enterprises advice and infrastructure. With successful community development and empowerment, it will lead to the benefit of the village itself, especially the community. So, this is considered a village's success in the capacity of civil society development. So that in accordance with the concept of problematic, namely everything that is useful, brings good, and rejects harm for the common good whose goal is for the welfare of society.